Respostas
respondido por:
0
X² + 2x - 8 = 0
b² - 4•a•c
2² - 4•1•(-8)
4 + 32
∆ = 36
∆>0 a equação terá duas raízes diferentes
- b ± √∆/2•a
-2 ± √36/2•1
x1 = 2 + 6/2 = 4
x2 = 2 - 6/2 = -2
Conjunto solução {-2,4}
b² - 4•a•c
2² - 4•1•(-8)
4 + 32
∆ = 36
∆>0 a equação terá duas raízes diferentes
- b ± √∆/2•a
-2 ± √36/2•1
x1 = 2 + 6/2 = 4
x2 = 2 - 6/2 = -2
Conjunto solução {-2,4}
respondido por:
1
Boa noite!
x² + 2x -8 = 0
ax² + bx + c = 0
a = 1
b = 2
c = -8
∆ = b² - 4ac
∆ = (2)² - 4 • 1 • (-8)
∆ = 4 + 32
∆ = 36
x'x" = {-b ± √∆} ÷ 2a
x'x" = {-2 ± √36} ÷ 2
x'x" = {-2 ± 6} ÷ 2
x' = (-2 + 6) ÷ 2 => x' = 2
x" = (-2 - 6) ÷ 2 => x" = -4
Abraço!!
x² + 2x -8 = 0
ax² + bx + c = 0
a = 1
b = 2
c = -8
∆ = b² - 4ac
∆ = (2)² - 4 • 1 • (-8)
∆ = 4 + 32
∆ = 36
x'x" = {-b ± √∆} ÷ 2a
x'x" = {-2 ± √36} ÷ 2
x'x" = {-2 ± 6} ÷ 2
x' = (-2 + 6) ÷ 2 => x' = 2
x" = (-2 - 6) ÷ 2 => x" = -4
Abraço!!
Perguntas similares
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás